Pengaruh Mekanisme Corporate Governance terhadap Manajemen Laba dengan Asimetri informasi sebagai Variabel Interveing - Nur Wahid Setiawan (El-Iqtishod: Jurnal Ekonomi Syariah, 2023)
This study aims to determine the effect of corporate governance mechanism (managerial ownership, institutional ownership, and audit committees) on earning management with information asymmetry as an intervening variable. The type of research is quantitative using secondary data in the form of data from the financial statements of company listed in Indonesia Sharia Stock Index (ISSI). The sampling method in this study uses purposive sampling with a sample of 78 companies listed in ISSI with 3 years period. Then the results obtained were processed with Eviews-12. The analysis used included descriptive statistical test, classical assumption test, path analysis regression test and hypothesis testing. Based on the test results obtained: managerial ownership does not have significant negative effect on earning management. Institutional ownership has a significant negative effect on earning management. Audit committees does not have negative effect significant on earning management. Information asymmetry has a positive significant effect on earning management. Managerial ownership does not have effect on information asymmetry. Institutional ownership has a negative significant on information asymmetry. Audit committees does not have effect on information asymmetry. Managerial ownership, institutional ownership and audit committees can mediate earning management with information asymmetry.